THE IMPACTS OF LEADERSHIP AND CULTURE ON WORK PERFORMANCE IN SERVICE COMPANY AND INNOVATIVE WORK BEHAVIOR AS MEDIATING EFFECTS - Agus Purwanto; Innocentius Bernarto; Masduki Asbari; Laksmi Mayesti Wijayanti; Choi Chi Hyun (Journal of Research in Business, Economics, and Education, 2020)
In today's highly competitive service world, many companies face rapid and dynamic changes, especially in the 4.0 industrial revolution. Therefore companies must focus on innovative work behavior (IWB) to gain competitive advantage. This study examines the effect of transformational leadership and company climate on work performance through innovative work behavior as mediation by taking a service company in Indonesia. Data collection methode is simple random sampling via electronic to the population of service employees in Indonesia. The returned and valid questionnaire results were 1199 samples. Data processing using SEM method with SmartPLS 3.0 software. Data collection techniques using a questionnaire with a Likert scale. The result of data analysis is that transformational leadership and corporate culture have positive and significant effects on work performance, both directly and indirectly through mediating innovative work behavior. Innovative work behavior has a very positive and significant effect on work performance. This new research proposes a model for building work performance among employees of transformational leadership companies and corporate culture with corporate learning as mediation